1989
DOI: 10.1093/ajcp/92.2.177
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Spectrum, Pathology, and Clonal Analysis of Epstein-Barr Virus–Associated Lymphoproliferative Disorders in Heart–Lung Transplant Recipients

Abstract: This study presents the clinical and laboratory observations on posttransplant lymphoproliferative disorders (PTLDs) occurring in 5 of 53 heart-lung transplantation recipients. Cervical lymph nodes, tonsils, lungs, and gastrointestinal tract were the common sites of involvement by PTLDs. The histopathologic findings showed a spectrum of lymphoid and immunoblastic proliferation ranging from diffuse hyperplasia to malignant lymphoma, immunoblastic or large cell type. All cases were associated with a primary Epst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(31 citation statements)
references
References 0 publications
3
27
1
Order By: Relevance
“…Posttransplantation lymphoproliferative disorder (PTLD) is a potentially lethal complication of immunosuppression in solid organ transplant (SOT) and bone marrow transplant (BMT) recipients, [1][2][3] mostly associated with the proliferation of Epstein-Barr virus (EBV)-infected B cells whose expansion in immunocompetent individuals is controlled by cytotoxic T lymphocytes (CTLs). 4 There is ample evidence that an adoptive immunotherapy approach with transfer of lymphocytes or EBV-specific CTLs of donor origin is effective as prophylaxis and/or treatment of EBV-related PTLD in recipients of T-cell-depleted BMT [5][6][7][8] ; data have shown that anti-CD20 monoclonal antibody can be an equally useful therapeutic strategy when donor-derived EBV CTLs are not available.…”
Section: Introductionmentioning
confidence: 99%
“…Posttransplantation lymphoproliferative disorder (PTLD) is a potentially lethal complication of immunosuppression in solid organ transplant (SOT) and bone marrow transplant (BMT) recipients, [1][2][3] mostly associated with the proliferation of Epstein-Barr virus (EBV)-infected B cells whose expansion in immunocompetent individuals is controlled by cytotoxic T lymphocytes (CTLs). 4 There is ample evidence that an adoptive immunotherapy approach with transfer of lymphocytes or EBV-specific CTLs of donor origin is effective as prophylaxis and/or treatment of EBV-related PTLD in recipients of T-cell-depleted BMT [5][6][7][8] ; data have shown that anti-CD20 monoclonal antibody can be an equally useful therapeutic strategy when donor-derived EBV CTLs are not available.…”
Section: Introductionmentioning
confidence: 99%
“…1,[3][4][5][6] These tumors frequently involve extranodal sites and generally regress with reduction or withdrawal of immunosuppressive therapy, but some of them progress independently from the restoration of the immune system. It has been hypothesized that PT-LPDs arise from a polyclonal expansion of Epstein-Barr virus (EBV)-infected B cells and can evolve into a lymphoid tumor with the emergence of an oligoclonal or monoclonal dominant population.…”
mentioning
confidence: 99%
“…Integration of EBV into B-lymphocytes might result in some risk for the development of lymphoproliferative disorders later in life. EBV-associated diffuse lymphoid proliferations have been observed to occur in the lungs of patients treated with immunosuppressive therapy after organ transplantation [24,25]. Patients with various types of immunodeficiency are at increased risk for the development of potentially fatal EBV-related lymphoproliferative diseases, B lymphomas, and severe atypical EBV infections; most notably, this includes male children with the x-linked lymphoproliferative syndrome [26].…”
Section: Discussionmentioning
confidence: 99%